Effects of a nutrition education programme on knowledge, attitude, and practice of physical activity and nutrition among female adolescents in Saudi Arabia - Bahathig, Abeer Ahmad A (2022)
Obesity and non-communicable diseases (NCDs) are associated with physical inactivity, sedentary behaviour (SB), unhealthy food consumption, disordered eating (DE) behaviour and body image (BI) dissatisfaction amongst young adolescents. Nevertheless, nutrition education programmes (NEPs) offered to young Saudi adolescents remain limited. This study determines the effects of a NEP on the knowledge, attitude and practice (KAP) of physical activity, nutrition and body image amongst young female adolescents in Arar, Saudi Arabia. Phase 1 of this work is a cross-sectional study involving 399 participants randomly selected from four schools and subjected to questionnaire and anthropometric measurements. The results (Phase 1) showed that 13% and 2.5% of the participants were overweight and obese, respectively, 88.5% had low physical activity (PA) and ≥90% had high SB levels during weekends and weekdays. Moreover, most of the participants (89.7%) consumed excessive amounts of fat. DE was reported by 39.1% of the participants, and 18.5% reported BI satisfaction (BIS). Therefore, a NEP must be offered to female adolescents in Arar to improve their knowledge and behaviour towards PA, nutrition and BI. Phase 2 involves a cluster randomised controlled trial wherein schools and participants were randomly selected and assigned either to the intervention group (IG; n=68) or the control group (CG; n=70). The NEP consisted of a 60-minute seminar designed for the mothers of those students assigned to the IG; the seminar aims to help the mothers encourage their daughters to engage in PA, to eat healthy food and to display a positive BI. The IG received six 90- minute educational sessions on PA, nutrition and BI within three months, whereas the CG received the usual lessons. Both groups were assessed at baseline, during the posttest and at follow-up with the use of valid and reliable questionnaires prepared in the native language. A generalised estimating equation test and an interaction effect test (Time*Group) across time were conducted. The results showed that in the IG, there was an increase in the percentage of participants who engaged in vigorous PAs and who demonstrated reduced SB. Moreover, the knowledge, attitude, and practice (primary outcomes) of the IG significantly changed relative to those of the CG from the baseline to follow up, with mean differences of −16.27, −51.33 and −35.20, respectively; moreover, the Time*Group interaction was significant (p<0.001). The IG also significantly differed from the CG in terms of secondary outcomes, namely, PA, SB during weekdays and weekends; consumption of dairy products, sweetened beverages, sweetened baked goods, and fruits and vegetables (p<0.05); DE (p≤0.001), except for bulimia; and BIS (p<0.001). The BMI-for-age z-score, waist circumference and energy and macronutrient intake did not significantly differ (p>0.05) between the groups. In summary, the NEP effectively improved the KAP, PA, dietary intake and BIS and decreased the SB and DE amongst the female adolescents in Arar. These results demonstrated the soundness of integrating the NEP into the Saudi curriculum to increase the awareness of young Saudi female adolescents about PA, nutrition and BI in order to reduce the prevalence of obesity and NCDs.